Maqashid Syari'ah in Practical Sustainability Report: A Case Study of BUMN in South Sumatra - Muhammad Farhan; Media Kusumawardani; Abdul Bashir; Achmad Soediro (Faculty of Economics, Universitas Sriwijaya, 2021)
The purpose of this study was to determine the effect of economic, environmental and social aspects on the form of disclosure of maqashid syari’ah in the sustainability report company’s. The data used is individual data with a sample of 352 people who work for state-owned companies operating in the South Sumatra region. This study uses quantitative methods by applying multiple linear regression models. The findings in this study indicate that jointly the indicators adopted from the Global Reporting Initiative (GRI) grouped on economic, environmental, and social aspects have a significant and positive effect on the disclosure of Maqashid Syari'ah in the sustainability reports. The implication of this research implicitly reveals that GRI indicators covering economic, environmental, and social aspects in companies have a big role in realizing goodness while avoiding bad, or benefit (maslahat) and rejecting madharat